Explicit Formula
Just in case you don't know what this is, the explicit formula is the formula that solves for any term in the series without necessarily knowing what came before the term you are solving.
<em><u>Givens</u></em>
d = t_(n + 1) - t_n You can take any term and the next term for this part of the formula
d = t_3 - t_2
t_3 = 1
t_2 = -7
d = 1 - - 7 = 8
a = -15
<em><u>Formula</u></em>
t_n = a + (n - 1)*d
t_n = -15 + (n - 1)*8
For example find the 5th term.
t_5 = - 15 + (5 - 1)*8
t_5 = - 15 + 4 *8
t_5 = -15 + 32
t_5 = 17 Which is what you have.
Recursive Formula
Computers really like this formula. They use it in what is called a subroutine and they pass values from one part of the program to a subroutine which evaluates the given and sends the result back. I'm telling you all this so you see why you are doing it. The disadvantage of it for humans is that you must know the preceding term to use the recursive formula.
<em><u>Formula</u></em>
t_n = t_(n - 1) + d
<em><u>Example</u></em>
t_6 = t_(6 - 1) + d
t_6 = t_5 + 8
t_6 = 17 + 8
t_6 = 25
You can check this by using the explicit formula.
Answer:
The answer is D.) Quadrant IV
Step-by-step explanation:
I took a quiz on this before and Quadrant IV was correct but I don't know if it's true because some of you're answers are different from mine but on my quiz D was the answer
<u>Answer:</u>
The equation of a line, in point slope form that passes through (-2, -6) and has a slope of 1/3 is 
<u>Solution:</u>
Given that line passes through (-2, -6) and has slope of 1/3
We have to find the equation of the line
The point slope form is given as

where m is the slope of the line and a, b are the x, y coordinates of the given point through which the line passes.
Here in this question, m = 1/3 and a = -2 and b = -6
By substituting in point slope form we get,

Hence the equation of a line, in point slope form that passes through (-2, -6) and has a slope of 1/3 is 
Answer:
The answer is 22.5 miles
Step-by-step excplanation:
Answer:
See answer below
Step-by-step explanation:
For the first expression
3 x (x - 2) + 2 = 3 x^2 - 6 x + 2
evaluated at x= 4 we get: 26
and for x = 5 we get 47.
For the second expression
2 x^2 + 3 x - 18
we get the exact same values when doing the evaluation at these two points.
Based on those results, one may think the expressions may be equivalent, but they are not equivalent. Because at any other x-value, their results are different. See for example that for x = 0 the first one gives "2" while the second one gives -18.